Using a sustainable food systems framework to examine gender equality and women’s empowerment in aquatic food systems - Adam, Rahma; Dam Lam, Rodolfo; Lozano, Denise; McDougall, Cynthia; Rajaratnam, Surendran; Ouko, Kevin; Manyungwa-Pasani, Chikondi; Forsythe, Lora; Rossignoli, Cristiano (Frontiers Media S.A., 2024)
This article aims to generate novel insights by examining gender dynamics within aquaculture and small-scale fisheries, employing a gendered agrifood systems conceptual framework to comprehensively analyze gender equality and women’s empowerment in aquatic food systems. To do this, it evaluates 202 articles using a scoping review methodology. Though additional literature from 19 articles was pulled in to provide the context. The findings are that aquatic foods value chains and food environment are negatively impacted by gender disparities in terms of women’s agency, access to and control over resources, gendered social norms, and policies and governance. This hampers the ability of women to engage in and benefit from aquatic food systems. This results in gendered disparities in dietary outcomes, low achievements in relation to gender equality and women’s empowerment, and less adaptive capacity in relation to developing resilient livelihoods. The article acknowledges the importance of developing and leveraging women’s agency and bargaining power, strengthening their access to and control over key aquatic food systems resources, tackling harmful gender norms, developing gender-sensitive data collection and analysis to inform evidence-based policymaking, and implementing gender-responsive and gender-transformative policies and strategies to create an enabling environment for these interventions to succeed. Investment in multi-level, and multi-layered, gender-responsive and gender-transformative approaches are needed to co-develop – with women and their organizations – positive, gender-equitable norms to strengthen women’s agency and decision-making at a variety of levels, ranging from individual to policy level.